Mapping Knowledge Structure and Themes Trends of Osteoporosis in Rheumatoid Arthritis: A Bibliometric Analysis - Wu, Haiyang; Cheng, Kunming; Guo, Qiang; Yang, Weiguang; Tong, Linjian; Wang, Yulin; Sun, Zhiming (Frontiers in Medicine, 2021)
Background: Rheumatoid arthritis (RA) is a chronic disabling disease characterized by chronic inflammation, articular cartilage destruction and reduced bone mass. Multiple studies have revealed that the development of osteoporosis in RA (ORA) patients could led to the reduced quality of life and increased healthcare costs. Nevertheless, no attempt has been made to analyze the field of ORA research with bibliometric method. This study aims to provide a comprehensive overview of the knowledge structure and theme trends in the field of ORA research from a bibliometric perspective. Methods: Articles and reviews regarding ORA from 1998 and 2021 were identified from the Web of Science database. An online bibliometric platform, CiteSpace and VOSviewer software were used to generate visualization knowledge maps including co-authorship, co-citation, and co-occurrence analysis. SPSS, R, and Microsoft Excel software were used to conduct curve fitting and correlation analysis, and to analyze quantitative indicators, such as publication and citation counts, h-index, and journal citation reports. Results: A total of 1081 papers with 28473 citations were identified. Publications were mainly concentrated in North America, Western Europe and Eastern Asia. Economic strength is an important factor affecting scientific output. The United States contributed the most publications (213) with the highest h-index value (46) as of September 14, 2021. Diakonhjemmet Hospital, and professor Haugeberg G were the most prolific institution and influential author, respectively. Journal of Rheumatology was the most productive journal concerning ORA research. According to the burst references, “anti-citrullinated protein antibodies” and “preventing joint destruction” have been recognized as the hot research issues in the domain. The keywords co-occurrence analysis identified “teriparatide”, “interleukin-6”, “Wnt”, and “vertebral fractures” as the important future research directions. Conclusion: This is the first bibliometric study comprehensively summarizing the trends and development on ORA research. Our findings could offer practical sources for scholars to understand the key information in this field, and identify the potential research frontiers and hot directions in the near future.